Communication Identity Formation of Shariah-Compliant Make-Up Artists as Micro-Entrepreneurs - Maret Pujiasih; Indra Novianto Adibayu Pamungkas (INJECT (Interdisciplinary Journal of Communication), 2026)
This study examines the communication identity formation of Shari'i-compliant Make-Up Artists (MUAs) as micro-entrepreneurs in West Java, Indonesia. It aims to understand how MUAs negotiate personal religious values with professional demands in the beauty industry, and how such negotiation shapes their communication practices and professional identity. The study contributes to communication scholarship by exploring religiously-informed professional identity, providing insights for micro-entrepreneurs and digital marketing strategies in creative sectors. A qualitative phenomenological approach was adopted to capture the subjective experiences of ten female MUAs who implement Shari'i principles in their services and social media promotion. Data were collected through semi-structured interviews, digital observations, and documentation, and analyzed using thematic analysis supported by NVivo 12 Plus. Data validity was ensured through triangulation and member checking. Findings indicate that MUA Shari'i identity is structured across four interconnected layers—personal, enacted, relational, and communal—forming a dynamic yet coherent communication identity. Personal identity is dominated by religiosity, reflection, and adaptation; enacted identity reflects discipline, consistency, and situational flexibility; relational identity emphasizes professionalism, empathy, and persuasive communication with clients; and communal identity is reinforced through social recognition, collaboration, and moderation in practice. The integration of these layers generates adaptive, collaborative, reliable, and visionary communicative traits, allowing MUAs to maintain religious integrity while achieving professional credibility and sustainable business practices. These results extend the Communication Theory of Identity (CTI) framework to contexts of religiously-informed micro-entrepreneurship, demonstrating the strategic role of personal and communal values in shaping professional communication.